Targeted Transthoracic Acoustic Activation of Systemically Administered Nanodroplets to Detect Myocardial Perfusion Abnormalities. (January 2016) - Porter, Thomas R.; Arena, Christopher; Sayyed, Samer; Lof, John; High, Robin R.; Xie, Feng; Dayton, Paul A.
Abstract : Background—: Liquid core nanodroplets containing condensed gaseous fluorocarbons can be vaporized at clinically relevant acoustic energies and have been hypothesized as an alternative ultrasound contrast agent instead of gas-core agents. The potential for targeted activation and imaging of these agents was tested with droplets formulated from liquid octafluoropropane (C3) and 1:1 mixtures of C3 with liquid decafluorobutane (C3C4). Methods and Results—: In 8 pigs with recent myocardial infarction and variable degrees of reperfusion, transthoracic acoustic activation was attempted using 1.3 to 1.7 MHz low (0.2 mechanical index [MI]) or high MI (1.2 MI) imaging in real time (32–64 Hertz) or triggered 1:1 at end systole during a 20% C3 or C3C4 droplet infusion. Any perfusion defects observed were measured and correlated with delayed enhancement magnetic resonance imaging and postmortem staining. No myocardial contrast was produced with any imaging setting when using C3C4 droplets or C3 droplets during low MI real-time imaging. However, myocardial contrast was observed in all 8 pigs with C3 droplets when using triggered high MI imaging and in 5 of 6 pigs that had 1.7 MHz real time-high MI imaging. Although quantitative myocardial contrast was lower with real-time high MI imaging than 1:1 triggering, the correlation between real-time resting defect size and infarct size was good ( r =0.97; P <0.001), as was the correlation with number of transmural infarcted segments by delayed enhancement imaging. Conclusions—: Targeted transthoracic acoustic activation of infused intravenous C3 nanodroplets is effective, resulting in echogenic and persistent microbubbles which provide real-time high MI visualization of perfusion defects. Abstract : Supplemental Digital Content is available in the text.